Regional integration in Latin America and dynamic gains for macroeconomic cooperation - Escaith, Hubert (ECLAC SantiagoCL, 2003)
Presents some of the most important concepts behind the potential dynamic welfare gains to be obtained from macroeconomic policy cooperation in Latin America and the Caribbean.